Argumentasi dalam Teks Pidato Mahasiswa - Dedi Gunawan Saputra; Dawud Dawud; Imam Agus Basuki (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: Argumentation is closely related to a person's mindset to achieve communication goals. The focus of this research is the argumentation component, the argumentation model, and the argumentation writing style. The data of this research are in the form of words, sentences, and paragraphs from the students' speech texts of undergraduate students of Indonesian Language and Literature Education, Universitas Negeri Malang. Undergraduate students who are used as data sources are students for the 2019/2020 academic year. The results showed that the arguments in the speech texts of Indonesian Language and Literature Education students at the Universitas Negeri Malang contained various components, models, and styles of argumentative writing. These three things have been constructed by students in the speech text. These components, models, and writing styles have a concrete form and their respective functions in strengthening the arguments put forward in the speech texts.Abstrak: Argumentasi berkaitan erat dengan pola pikir seseorang untuk mencapai tujuan komunikasi. Adapun fokus penelitian ini, yaitu komponen argumentasi, model argumentasi, dan gaya penulisan argumentasi. Data penelitian ini berupa kata, kalimat, dan paragraf dari teks pidato mahasiswa S1 Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Malang. Mahasiswa S1 yang dijadikan sumber data merupakan mahasiswa tahun ajaran 2019/2020. Hasil penelitian menunjukkan bahwa argumentasi dalam teks pidato mahasiswa Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Malang memuat komponen, model, dan gaya penulisan argumentasi yang bervariasi. Ketiga hal tersebut telah dikonstruksikan oleh mahasiswa dalam teks pidato. Komponen, model, dan gaya penulisan tersebut memiliki bentuk konkret dan fungsi masing-masing dalam memperkuat argumentasi yang dikemukakan dalam teks pidato.